2022
DOI: 10.1186/s13007-022-00841-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of Ralstonia solanacearum infection progress in tomato and Arabidopsis using bioluminescence imaging technology

Abstract: Background Ralstonia solanacearum, one of the most devastating bacterial plant pathogens, is the causal agent of bacterial wilt. Recently, several studies on resistance to bacterial wilt have been conducted using the Arabidopsis-R. solanacearum system. However, the progress of R. solanacearum infection in Arabidopsis is still unclear. Results We generated a bioluminescent R. solanacearum by expressing plasmid-based luxCDABE. Expression of luxCDABE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Bacterial wilt, caused by R. solanacearum, is one of the most devastating bacterial diseases worldwide. 44 Use of nonpathogenic mutants of pathogens as biocontrol agents have been studied for decades. 11 The avirulent strain FJAT1458 is a potential biocontrol agent of BW.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial wilt, caused by R. solanacearum, is one of the most devastating bacterial diseases worldwide. 44 Use of nonpathogenic mutants of pathogens as biocontrol agents have been studied for decades. 11 The avirulent strain FJAT1458 is a potential biocontrol agent of BW.…”
Section: Discussionmentioning
confidence: 99%
“…A schematic diagram describing this relationship is shown in Figure 3B. Numerous studies showed a linear or near-linear relationship between the bacterial concentration in water and the bioluminescence intensity (Bozorg et al, 2015;Xu et al, 2022). However, we extended the linear relation to bacteria enumeration in sand media.…”
Section: Statistical Analysismentioning
confidence: 93%
“… Ralstonia solanacearum , which is the causal pathogen of bacterial wilt disease, infects more than 250 plant species, most of which belong to the Solanaceae family, including pepper, tobacco, tomato, and potato ( 1 , 2 ). R. solanacearum invades the xylem vessels through plant root hairs and disseminates into the stem, where it multiplies and causes wilting by blocking water transport and producing excessive exopolysaccharides ( 3 ).…”
Section: Announcementmentioning
confidence: 99%